Are bitcoin and gold safe haven assets? Evidence from Thailand - Prukumpai, Suthawan; Sethapramote, Yuthana (Kasetsart Journal of Social Sciences, 2023)
This paper aims to investigate the role of Bitcoin and gold in equity portfolio formation. The dynamic relationships among four asset classes: Bitcoin, gold, equities, and bonds are examined, using Thai data from April 30, 2013 to February 27, 2021. The dynamic conditional correlations based on the DCCGARCH model show that stock-gold correlations are generally negative while stock-Bitcoin correlations are close to zero. Interestingly, stock-bond correlations display the highest value over time. The spillover indices also show that gold and Bitcoin are less connected with stock while bonds receive the largest spillover from stock. To formally test which assets can be used as a safe haven against stock, dummy variable regression models with three different dependent variables: namely asset returns, DCCs, and pairwise spillovers are estimated. The results from the dummy variable regressions reveal that only gold acts as a safe haven for Thai equity portfolio. Moreover, Bitcoin and bonds tend to provide weaker diversification benefits than gold.